If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -24 = -32 + 9x Reorder the terms: -24 + 5x = -32 + 9x Solving -24 + 5x = -32 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -24 + 5x + -9x = -32 + 9x + -9x Combine like terms: 5x + -9x = -4x -24 + -4x = -32 + 9x + -9x Combine like terms: 9x + -9x = 0 -24 + -4x = -32 + 0 -24 + -4x = -32 Add '24' to each side of the equation. -24 + 24 + -4x = -32 + 24 Combine like terms: -24 + 24 = 0 0 + -4x = -32 + 24 -4x = -32 + 24 Combine like terms: -32 + 24 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| 2x-1y=-34 | | 24x^2+62x+14= | | -9(-4v+4)+-3v+-6= | | (y-2)(y-1)=2(y-2)(y-3) | | 6x^4-20x^3+16x^2= | | 3x-5b=10x | | Y^2-18Y+45=O | | log(7x+6)=2 | | 2a-3=16 | | 42q^2+17qd-15d^2= | | x(x^2-5x-6)=0 | | 10+9(8+5c)= | | f(x)=3x^2-2x+6 | | x+28=25 | | 56v^2+17vb-3b^2= | | 8+2x-4=6+4(x-1) | | 8+2x-4=6+4 | | -5(-9+-10t)+10(3+-5t)= | | 3[x+2(x-7)]=-60 | | 5x+28=35 | | 6-(-5)r=5r-3 | | -9(-1+-4k)+k= | | 2(x+4)=6-1(3x-2)-1 | | Y=log[4](x^2-4x-21) | | x-7=-.25 | | 8x-29=-77+2x | | 7x-28=17+2x | | 2(6x+6)+8=8x+18 | | 3(2a-2)=2(3a-3) | | 5(3+6x)-4=41 | | 6x^2+33x+42=0 | | x^2-2x+56=0 |